Antimicrobial Peptides from Porcine Blood Cruor Hydrolysates as a Promising Source of Antifungal Activity - Sara García-Vela; Aurore Cournoyer; Zain Sánchez-Reinoso; Laurent Bazinet (Foods)
Porcine blood, a significant byproduct of the pork industry, represents a potential source of antimicrobial peptides (AMPs). AMPs offer a promising alternative to chemical antimicrobials, which can be used as natural preservatives in the food industry. AMPs can exhibit both antibacterial and/or antifungal properties, thus improving food safety and addressing the growing concern of antibiotic and antifungal resistance. The objective of this study was to evaluate the antimicrobial activity of potential AMPs previously identified from porcine cruor hydrolysates. To this end, a total of sixteen peptides were chemically synthesized and their antimicrobial activities (antibacterial, anti-mold, and anti-yeast) were evaluated using microtitration and agar well diffusion methods against a wide range of microorganisms. Five new peptide sequences demonstrated antifungal activity, with Pep5 (FQKVVAGVANALAHKYH), an alpha-helix peptide, exhibiting the most promising results. Pep5 demonstrated efficacy against nine of the eleven fungal isolates, exhibiting low minimum inhibitory concentrations (MICs) and a fungicidal effect against key spoilage fungi (Rhodotorula mucilaginosa, Debaryomyces hansenii, Candida guilliermondii, Paecilomyces spp., Eurotium rubrum, Mucor racemosus, Aspergillus versicolor, Penicillium commune, and P. chrysogenum). These findings illustrate the potential of porcine blood hydrolysates as a source of AMPs, particularly antifungal peptides, which are less known and less studied than the antibacterial ones. Among the tested sequences, Pep5 exhibited the most promising characteristics, including broad-spectrum activity, low MICs, and a fungicidal effect. It is, therefore, a promising candidate for further research and for potential applications in the porcine industry and beyond.